2004
DOI: 10.1111/j.1365-2621.2004.00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Flavour sensory qualities and consumer perceptions – a comparison of sensory and brain activity responses to flavour components in different populations

Abstract: This paper explores the relationship between odour responses of naı¨ve consumers to different flavour components, by investigating the ability of sensory ratings and brain recording techniques to reveal differences in responses associated with differences in background and experience. Two groups of naı¨ve consumers (Australian and Overseas students from Asian/South-east Asian background; all untrained in sensory work) participated in sensory ratings and brain electrical activity [electroencephalogram (EEG)] re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Watanuki and Kim [92] found that the beta wave activity increased in the left frontal brain region due to a pleasant odor. Patterson et al [93] examined the relationship between odor responses of consumers to different flavor components ( para -cresol 4-methylphenol, 2-heptanone, methional, 3-methylthiopropionaldehyde and dimethyltrisulphide). The authors suggested an ability of sensory ratings and brain recording techniques to reveal differences in responses associated with variations in background and experience.…”
Section: Effect Of Inhalation Of Fragrance On Eeg Activitymentioning
confidence: 99%
“…Watanuki and Kim [92] found that the beta wave activity increased in the left frontal brain region due to a pleasant odor. Patterson et al [93] examined the relationship between odor responses of consumers to different flavor components ( para -cresol 4-methylphenol, 2-heptanone, methional, 3-methylthiopropionaldehyde and dimethyltrisulphide). The authors suggested an ability of sensory ratings and brain recording techniques to reveal differences in responses associated with variations in background and experience.…”
Section: Effect Of Inhalation Of Fragrance On Eeg Activitymentioning
confidence: 99%
“…MB preparations were introduced to untrained panelists from the staff and master students of Nutrition and Food Technology Department at the University of Jordan. The sample temperature was around 15°C when introduced to the panelists who were asked to evaluate the overall acceptability of each sample using a nine-point hedonic scale test (Patterson et al 2004).…”
Section: Selection Of Optimal Formulamentioning
confidence: 99%
“…It can lead to either good or bad emotions when smelling or consuming food products. A change in the electroencephalographic (EEG) spectra can reveal a change in memory performance and the cognitive state (Patterson et al, 2004;Ndaro & Wang, 2018).). The relation between EEG results and the sensory properties of food products can provide helpful data to create emotions and affect decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…It can lead to either good or bad emotions when smelling or consuming food products. A change in the electroencephalographic (EEG) spectra can reveal a change in memory performance and the cognitive state (Patterson et al., 2004; Ndaro & Wang, 2018). ).…”
Section: Introductionmentioning
confidence: 99%